Atividade Fungicida de Novos Triazóis Sintetizados a Partir de Glicerol Sobre Fusarium Guttiforme - Silva, Márcia Varela da (2014)
The pathogen Fusarium guttiforme causes various damage to the culture of pineapple. The main strategy of disease management is the use of resistant varieties and spraying with fungicides, however there are few commercial products available, which has hind